Autonomic Dysfunction in Children with Acute Community-Acquired Pneumonia and the Ways of Drug Treatment - S.L. Nyankovsky; M.S. Yatsula; I.V. Babik; O.I. Shpychka; L.O. Movyak (Zaslavsky O.Yu., 2012)
The paper deals with the features of clinical course, intensity of toxic, asthenic syndromes, autonomic functioning in children of 7 years old with signs of community-acquired pneumonia based on instrumental autonomic testing and EEG findings. The probiotic Enterol and metabolic medication Stimol included into the treatment scheme fasten normalization of clinical, instrumental and functional parameters, reduce autonomic dysfunction, improve physical condition, adaptive opportunities, stress resistance, reduce imbalance between humoral-metabolic and central ergotropic influence, normalize responsiveness of parasympathetic nervous system and balance of autonomic modulation of cardiac rhythm, improve EEG findings.